Financial Ratio Analysis to Predict Profit Changes in Transportation Companies Listed on the Indonesia Stock Exchange (IDX) - Husien, Fadhel; Takarini, Nurjanti (International Journal of Economics (IJEC), 2025)
During the 2019-2021 period, the world experienced a crisis due to the COVID-19 pandemic, which had a significant impact on various economic sectors, including transportation. Interestingly, this sector showed a contrasting trend, where social restrictions reduced community mobility activities but at the same time increased parcel delivery volumes due to the growth of online services. This study aims to evaluate the ability of changes in financial ratios—covering liquidity, profitability, leverage, activity, and market ratios—to predict earnings changes in 38 transportation companies listed on the Indonesian Stock Exchange during that period. Data analysis was performed using SPSS through a logistic regression method to assess the probability of the influence of each ratio on earnings changes. The results show that changes in liquidity, profitability, leverage, and activity ratios affect earnings changes, whereas changes in market ratios show no effect. These findings indicate that most fundamental ratios can serve as relevant indicators in predicting changes in the earnings performance of transportation companies during a crisis